Tingkat Kritis Intensitas Cahaya Relatif Lima Genotip Kacang Hijau (Vigna radiatus L.) - Titik Sundari; , Soemartono; , Tohari; W. Mangoendidjojo (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2005)
The aim of this experiment was to determine the critical relative light intensities (RLI) level of mungbean. The critical level was determined by 50% decreasing of grain yield. The experiment was conducted at the ILETRI (Indonesian Legume and Tuber Crops Research Institute), Malang, from February to May 2004. Five genotypes of mungbean, i.e. VC2768B, Kenari, Local Wongsorejo, Nuri and MLG 431 were grown in  four relative light intensities (RLI) levels, respectively 100%, 75%, 50% and 25%, that were prepared before planting with artificial shading. The experimental design was a randomized complete block with three replicates. The results showed that reducing RLI increased specific leaf area, but decreased leaf number, leaf area, leaf, stem and root dry weight, as well as pod number, pod dry weight and grain yield per plant. Reducing RLI from 100% to 75%, 50% and 25% did result in 15%, 56% and 71% decreased grain yield of mungbean. The critical level of RLI on mungbean was 48% or was found at 52% shading.   Key words: Vigna radiatus L., genotype, critical level, relative light intensities, growth, yield